Implementation of Green Accounting in Efforts to Prevent Environmental Pollution to Support Business Continuity - Zulhawati; Meiliyah Ariani (Universitas Teknologi Yogyakarta, 2023)
The application of the Green Accounting method is a discourse that is influenced and influences the environment. Accounting itself grows and develops along with the development of society. Environmental problems are not only a problem for regulators and the government as executors but also for economic actors to create an environmentally friendly mindset and attitude. One example is that many business owners still have a place of business but do not think about the impact of the generated business waste. This study aims to find out, analyze and provide conclusions about whether the waste of Batik Houses in the Kembangan area of ​​West Jakarta has a waste disposal mechanism. The costs incurred in waste treatment, find out the efforts of Batik Houses in dealing with environmental pollution and analyze the effectiveness and efficiency of Batik Houses in treating their waste if reviewed from an accounting perspective. Based on the results of the research, the waste of Batik Houses in the Kembangan area of ​​West Jakarta is still not efficient in managing the waste it produces because the managed waste treatment still has a negative impact on the surrounding community in terms of accounting for the efforts made by Batik Houses are still not effective in handling the results from the pollution of the waste they produce, this is proven by the absence of a clear financing analysis regarding the management of batik house waste so that it is not yet feasible in waste treatment.